2019
DOI: 10.1111/camh.12315
|View full text |Cite
|
Sign up to set email alerts
|

Debate Editorial: Very early onset bipolar disorder – international differences in prevalence, practice or language?

Abstract: Read the core debate at: doi: ; doi: ; doi: ; doi: Read more perspectives in this debate at: doi: doi: ; doi: ; doi: ; doi: ; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[R]ates of mania/bipolar I disorder are lower in both places than referenced by Van Meter, et al Van Meter and colleagues responded to our reanalysis, which prompted a nine-article debate section in CAMH (Carlson and Dubicka 2019;Duffy 2019;Goldstein et al 2019;Hazell 2019;Hillegers 2019;Pan et al 2019;Parry et al 2019a;Stringaris 2019;Van Meter et al 2019b). Duffy, lead researcher for the longitudinal Canadian high-risk offspring study, summarised research data and concluded (Duffy 2019):…”
Section: Prior Re-examination Of First Meta-analysis Of 'Pbd' Communi...mentioning
confidence: 89%
“…[R]ates of mania/bipolar I disorder are lower in both places than referenced by Van Meter, et al Van Meter and colleagues responded to our reanalysis, which prompted a nine-article debate section in CAMH (Carlson and Dubicka 2019;Duffy 2019;Goldstein et al 2019;Hazell 2019;Hillegers 2019;Pan et al 2019;Parry et al 2019a;Stringaris 2019;Van Meter et al 2019b). Duffy, lead researcher for the longitudinal Canadian high-risk offspring study, summarised research data and concluded (Duffy 2019):…”
Section: Prior Re-examination Of First Meta-analysis Of 'Pbd' Communi...mentioning
confidence: 89%
“…Further, studies have noted cross-cultural differences in diagnosis such that US psychiatrists conceptualize explosive temper, chronic behavioral and social and cognitive dysregulation/deficits as a form of bipolar disorder, while UK and EU psychiatrists preferential diagnose pervasive developmental disorder (not PBD). 49,50 On the other hand, one may argue that all included studies used validated diagnostic tools, such as the K-SADS, to categorize patient groups. Furthermore, we have previously shown that the diagnosis of PBD is stable over time.…”
Section: Limitations and Direction For Future Researchmentioning
confidence: 99%
“…Bipolar disorder is common in clinical psychiatric practice, and several studies have estimated its prevalence to range from 0.5 to 5% in community-based samples. (1) In South East Asia, the proportion of type I bipolar disorder is 0.6% and that of type II is 0.4%. (2) However, establishing the diagnosis in both children and adolescents is still challenging.…”
Section: Introductionmentioning
confidence: 99%